Niektóre przypadki kształtowania trójwarstwowych płyt swobodnie podpartych o równomiernej wytrzymałości - Dzieniszewski, W. (Engineering Transactions, 1969)
In this paper is formulated the problem of determining the varying thickness of external layers in three-layer plates of uniform strength. It is assumed that the thickness of the central layer is constant. The material of the external layers of the plate is elastic. The stresses arising in it due to the transverse load of the plate are determined according to energy hypotheses. The above problem leads to the problem of solving two equations containing partial derivatives: a nonlinear equation of the second order for the bending of the plate with uniform strength, and a Iinear equation of the second order with functional coefficients describing the thickness of the external plates with uniform strength. In the second equation the coefficients consist of the second derivatives of the bending function of the plate. These equations are solved for an elliptical plate uniformly loaded, and for some cases of rectangular plates. The solution for a square plate is illustrated by graphs of the varying thickness of the external layers.